Action: Efektivitas Acceptance and Commitment Therapy terhadap Resiliensi pada Remaja Bipolar - Aulia, Syarifah; Harisuci, Tinon Citraning (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the effect of Acceptance and Commitment Therapy (ACT) on resilience among adolescents with bipolar disorder. The research employed a mixed-methods approach with an explanatory sequential design. In the initial phase, five adolescents with bipolar disorder received ACT intervention through a one-group pretest-posttest model. The results showed a significant increase in resilience scores (t = -3.076, p = 0.037), with an average score difference of -35.8. Furthermore, the effect size calculation using Cohen’s d yielded a value of 1.38, which falls into the large category (d ≥ 0.80), indicating that the ACT intervention had a strong practical impact on enhancing resilience among adolescents with bipolar disorder. This finding was supported by in-depth interviews that revealed improvements in emotional regulation, self-awareness, life meaning, and self-reliance. Thus, ACT has been proven to contribute positively to the improvement of resilience in adolescents with bipolar disorder. The novelty of this study lies in the structured application of ACT to enhance resilience in bipolar adolescents, a topic that has rarely been studied in Indonesia. Practically, these findings are expected to provide an initial reference for the development of ACT-based psychological interventions in both clinical and community settings.